The needs of parents of hospitalized children: evidence for care - Rosyan Carvalho Andrade; Amanda Rossi Marques; Ana Carolina Andrade Biaggi Leite; Rafael Rozeta Martimiano; Bruna Domingos dos Santos; Raquel Pan; Ananda Maria Fernandes; Elsa Maria de Oliveira Pinheiro de Melo; Lucila Castanheira Nascimento (Universidade Federal de Goias, 2015)
Hospitalization has its benefits when treating sick children, but it can also cause negative impacts. Although it is essential and beneficial to the child, parental presence in the hospital ward destabilizes the family routine and generates new needs. The objective of this study was to search for evidence in the literature and identify, gather, and synthetize the knowledge that has been produced about the needs of parents of hospitalized children via an integrative literature review. The article search was conducted in the PubMed, CINAHL, PsycINFO, Scopus, Web of Science, and LILACS databases between 2002 and 2014 and resulted in 17 articles that met the established criteria. The parental needs found in these studies were grouped into three categories: the needs related to parents themselves, needs related to the health team's actions, and those related to organizational structure and resources. These needs were intimately interconnected, which means that accessing, assessing, and satisfying them must occur simultaneously, thus providing quality care to children and their families.